2008
DOI: 10.1016/j.jsbmb.2008.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Differential recruitment of glucocorticoid receptor phospho-isoforms to glucocorticoid-induced genes

Abstract: The human glucocorticoid receptor (GR) is phosphorylated on its N-terminus at three major sites (S203, S211 and S226) within activation function 1 (AF1). Although GR has been shown to assemble at glucocorticoid responsive elements (GREs) in the presence of hormone, the timing and specificity of GR phospho-isoform recruitment to receptor target genes has not been established. Using chromatin immunoprecipitation (ChIP) and GR phosphorylation site-specific antibodies, we examined GR phospho-isoform recruitment to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 111 publications
(92 citation statements)
references
References 28 publications
2
90
0
Order By: Relevance
“…Therefore, the GC response of genes that require pSer211-GR to reach peak activation may be altered in Cav-1 KO NPSCs. For example, pSer211-GR is recruited to promoters of genes such as Gilz and Tat to activate their transcription (29). Since GR phosphorylated at S211 is associated with activated gene transcription, alterations in pSer211-GR are consistent with the attenuated activation of select GR target genes in Cav-1 KO NPSCs.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Therefore, the GC response of genes that require pSer211-GR to reach peak activation may be altered in Cav-1 KO NPSCs. For example, pSer211-GR is recruited to promoters of genes such as Gilz and Tat to activate their transcription (29). Since GR phosphorylated at S211 is associated with activated gene transcription, alterations in pSer211-GR are consistent with the attenuated activation of select GR target genes in Cav-1 KO NPSCs.…”
Section: Discussionmentioning
confidence: 93%
“…In fact, different phosphorylation patterns within the amino-terminal activation function-1 domain can dictate which target genes will be bound by GR (29). Both MAPKs, targets of rapid GR signaling and cyclin-dependent kinase 2 (CDK2), phosphorylate GR and influence its transcriptional activity (39).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies showed that phosphorylation-deficient GR␣ mutants were compromised in their ability to activate reporter genes in a promoter-dependent fashion (79). Subsequently, it was reported that phosphorylation of Ser-211 correlated with the transcriptionally active form of GR␣, whereas phosphorylation of Ser-226 impaired its signaling capability (78,80,81). Phosphorylation of Ser-211 appears to be necessary for glucocorticoid-induced apoptosis of lymphoid cells, suggesting that a deficiency in this phosphorylation event may be a mechanism by which lymphocytes become resistant to glucocorticoids (82,83).…”
Section: Post-translational Modification Of Gr Isoformsmentioning
confidence: 99%